Substitusi Cpo Terhadap Asphalt Pen 60/70 Pada Campuran Asphalt Concrete Wearing Course (Ac-Wc) - Meidia Refiyanni; Azwanda Azwanda (Litbang Pemas - Universitas Islam Lamongan, 2020)
Asphalt 60/70 pen is a non-renewable natural resource so it is necessary to carry out continuous research in an effort to reduce the use of asphalt pen 60/70 which functions as a binder in the Asphalt Cement Wearing Course (AC-WC) mixture. This is due to the high demand for road construction to improve the economy. Crude Palm Oil (CPO) is a material which has almost the same properties with asphalt pen 60/70. Based on this background, the purpose of this study is to reduce the use of asphalt in the AC-WC mixture. This research method refers to the Department of Public Works, 2010 Specifications with gradations in meetings. This research was conducted with 2 variations, namely variation 1 (75% CPO: 25% Pen 60/70) KAO value 5.5% and variation 2 (25% CPO: 75% pen 60/70) KAO value 6%. The results of the study that fulfilled all Marshall parameters in the 30 minutes immersion test were variation 2: stability values of 803.38 kg, Flow 3.13 mm, VIM 4.17%, VMA 15.80%, VFB 73.59%, MQ 256,71 kg / mm. Meanwhile the stability value in the 24-hour immersion does not meet the requirements for both variations so that the impact on the value of durability does not meet the requirements of ≥ 90%. The durability value for variation 1 is 66% and variation 2 is 69%, this shows that the mixture of AC-WC with CPO substitution is not durable.